Modeling the Renewable Energy Transition in Canada Techno-economic Assessments for Energy Management - Ahmed, Tanveer (SpringerBriefs in Energy,, 2016)
The work demonstrates a techno-economic model of power generation for the cost-effective integration of renewable energy sources, with the goal of reducing greenhouse gas emissions in Canada. The methodological approach outlined by the author is based on periodic simulation of price variations. The result demonstrates that a 10% transition to renewable energy generation is possible, practical and affordable when supported by an effective policy framework that does not need to introduce a feed-in tariff or loan-based financial mode.